Pengaruh Investment Opportunity Set, Free Cash Flow, Struktur Modal, Profitabilitas Dan Likuiditas Terhadap Kebijakan Dividen (Studi Empiris pada Perusahaan Manufaktur yang terdaftar di Bursa Efek Indonesia Tahun 2012-2014) - Dewi, Aqlima Cendera (2016)
The objective of the research is to examine the influence of investment opportunity set, free cash flow, debt to equity ratio, return on asset and current ratio toward dividend policy. The population in this research is that all company including manufacturing sector in 2012-2014. The sampling technique employed was purposive sampling and accuired 96 companies during 3 years observation period. Data were provided by Indonesian Capital Market Directory (ICMD) and www.idx.co.id. The analysis technique employed was multiple regression. The result of this research finds that free cash flow and return on asset gives significant influence on dividend policy. The other variables which is investment opportunity set, debt to equity ratio and current ratio do not gives significant influence on dividend policy. From the observation result can be concluded that all of independent variable such as investment opportunity set, free cash flow, debt to equity ratio, return on asset and current ratio simultaneously nd significantly the dependent variable, dividend policy. Meanwhile the variables influence dividend policy partially include free cash flow and return on asset